Performance of sterilized Eldana saccharina Walker (Lepidoptera: Pyralidae) adults in mating and cage trials : further steps towards its control using the Sterile Insect Technique - Mudavanhu, Pride (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(Agric))--Stellenbosch University, 2012.